Pengaruh Profitabilitas, Likuiditas, Aktivitas, Leverage, dan Sales Growth Terhadap Financial Distress - Nurul Delayanti Dwi Oktaviani; G.Anggana Lisiantara (Owner : Riset dan Jurnal Akuntansi, 2022)
Financial distress is a situation where a company experiences financial difficulties before going bankrupt. The purpose of this study was to examine the effect of profitability, liquidity, activity, leverage and sales growth on financial distress in service companies in the tourism, restaurant and hotel sub-sectors listed on the Indonesia Stock Exchange (IDX). The sampling technique used documentation with secondary data obtained from the official website of the Indonesia Stock Exchange (IDX), namely www.idx.co.id. The number of samples used is 72. The method used in this study is purpose sampling. The data analysis technique used logistic regression analysis using the Eviews12 program. The partial results of this study explain that profitability has a negative influence on financial distress, then liquidity, activity, leverage and sales growth have no effect on financial distress. Keywords: Financial Distress; Profitability; Liquidity; Activity; Leverage; Sales Growth